ANALISIS IMPLEMENTASI KEBIJAKAN RELAKSASI KREDIT PADA MASA PANDEMI COVID-19 DI PT. BANK RAKYAT INDONESIA (PERSERO) TBK. - Septiyaning, Tuhindika (Jurnal Kompetitif Bisnis, 2020)
Covid 19 which emerged and spread among Indonesian people at the beginning of March 2020, has taken the attention of all strata of society in the face of this pandemic. The impact of Covid 19 is not only felt by the government, entrepreneurs, investors, but also by the community. Mainly related to government policy in overcoming the impact of Covid 19 on credit easing in the face of national economic turmoil. The credit relaxation policy has been supported by BUMN/D and Non BUMN/D banks. Including Bank Rakyat Indonesia Tbk, which implemented credit relaxation since the policy was set by the government. The application of credit relaxation BRI makes changes to profitability ratios, company performance and UMKM sector performance. The research method used is descriptive by describing phenomena and existing literature.